Effect of sugar apple ( annona squamosa) leaf extract as a feed additive on growth, feed utilization and health status in tilapia (oreochromis mossambicus) - Tessy, K. S. (KUFOS, 2019)
In the present study, six diets were formulated to contain 0, 1, 1.5, 2, 2.5 and 3 % Annonasquamosa leaf extract. Fifteen Oreochromismossambicus fry (38.4 ± 0.13 g) were stocked in each tank of 100 Lcapacity. Total 18 experimental tanks were used and three tanks were allocated under each dietary treatment. The water quality parameters like PH, DO, and temperature and ammonia nitrogen as well as growth response were monitored weekly basis. Periodical siphoning and 50 % water exchange maintained the water quality parameters at optimum range and it help to keep 100% survivability. The group fed diet with 2.5% leaf extract showed significant increase (P<0.05)in final weight (195.33±2.6g), weight gain (157±3.2g),weight gain percentage (408±14.9), SGR(2.7±0.04),CF(1.83±0.003), HSI(1.50±0.07), TGC(14.06±0.26).The nutrient utilization factors like FCR, FCE,PER, PRE and LRE also showed significant increase as compared with other groups. The proximate composition of the fish show no significant difference among the 6 treatments, except crude lipid that was high in group fed with2.5% leaf extract. Most of the hematological parameters (total protein, albumin, SGOT, SGPT, Alkaline phosphatase) was high in T4 group (group fed with 2.5% leaf extract). Other blood biochemical constituents like cholesterol, triglycerides and VLDL was high in fish fed with 3% leaf extract. Blood glucose concentration were high in control group. Percentage activity of antioxidants, SOD and glutathione peroxidase was high T5 (diet with 3% extract) and T4 group respectively.Digestive enzyme activity (amylase and protease) showed it higher activity in anterior intestine than middle and posterior intestine. The two digestive enzyme activities showed significant increase in T4 and T5 group. Among the six treatments groups all the tested parameters was lowest in group fed diet with 1% leaf extract. So it could be concluded that incorporation of Annonasquamosa aqueous leaf extract in fish diet improves its growth, nutrient utilization and health in Oreochromismossambicus.